Efficient Room-Temperature Phosphorescence from Discrete Molecules Based on Thianthrene Derivatives for Oxygen Sensing and Detection - Yang, Zhiqiang; Zhao, Shuaiqiang; Zhang, Xiangyu; Liu, Meng; Liu, Haichao; Yang, Bing (Frontiers in Chemistry, 2022)
In this work, two thianthrene (TA) derivatives, TA1P and TA2P, were synthesized with single phenyl modification for pure organic discrete-molecule room-temperature phosphorescence (RTP). They both show the dual emission of fluorescence and RTP in amorphous polymer matrix after deoxygenation, as a result of a new mechanism of folding-induced spin-orbit coupling (SOC) enhancement. Compared with TA1P, TA2P exhibits a higher RTP efficiency and a larger spectral separation between fluorescence and RTP, which is ascribed to the substituent effect of TA at 2-position. With decreasing oxygen concentration from 1.61% to 0, the discrete-molecule TA2P shows an about 18-fold increase in RTP intensity and an almost constant fluorescence intensity, which can make TA2P as a self-reference ratiometric optical oxygen sensing probe at low oxygen concentrations. The oxygen quenching constant (KSV) of TA2P is estimated as high as 10.22 KPa-1 for polymethyl methacrylate (PMMA) doped film, and even reach up to 111.86 KPa-1 for Zeonex® doped film, which demonstrates a very high sensitivity in oxygen sensing and detection. This work provides a new idea to design pure organic discrete-molecule RTP materials with high efficiency, and TA derivatives show a potential to be applied in quantitative detection of oxygen as a new-generation optical oxygen-sensing material.